Analisis SWOT dalam Meningkatkan Daya Saing pada Toko Dura di Bandar Lampung - Defrizal; Simeon Fabian Pramudya (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
This study aims to determine the marketing plan of Toko Dura to increase its competitiveness. The research methodology is descriptive analysis, SWOT analysis, External Factor Evaluation (EFE matrix), and Internal Factor Evaluation (IFE Matrix) were all used in this study. The study findings explain that Dura Store's competitive tactics are not only offering high-quality goods at low prices, but also considering delivery services, maximizing the marketing of goods through social media, and upholding the industry's reputation in society to foster consumer confidence. The IFE matrix for Dura Store is 2.86 which indicates a very strong internal position. The weight value of the EFE Matrix is 3.21 which shows that Toko Dura is relatively strong in resisting the dynamics of the external environment.